A genome-wide scan for schizophrenia and psychosis susceptibility loci in families of Mexican and Central American ancestry - Escamilla, Michael A. (2006)
Schizophrenia is a complex psychiatric disorder, likely to be caused in part by multiple genes. In this study, linkage analyses were performed to identify chromosomal regions most likely to be associated with schizophrenia and psychosis in multiplex families of Mexican and Central American origin. Four hundred and fifty-nine individuals from 99 families, containing at least two siblings with hospital diagnoses of schizophrenia or schizoaffective disorder, were genotyped. Four hundred and four microsatellite markers were genotyped for all individuals and multipoint non-parametric linkage analyses were performed using broad (any psychosis) and narrow (schizophrenia and schizoaffective disorder) models. Under the broad model, three chromosomal regions (1pter-p36, 5q35, and 18p11) exhibited evidence of linkage with non-parametric lod (NPL) scores greater than 2.7 (equivalent to empirical P values of less than 0.001) with the peak multipoint NPL = 3.42 (empirical P value = 0.00003), meeting genomewide evidence for significant linkage in the 1pter-p36 region. Under the narrow model, the same three loci showed (non-significant) evidence of linkage. These linkage findings (1pter-p36, 18p11, and 5q35) highlight where genes for psychosis and schizophrenia are most likely to be found in persons of Mexican and Central American ancestry, and correspond to recent linkages of schizophrenia or psychosis in other populations which were formed in part from emigrants from the Spanish empire of the 15th and 16th centuries.